The Correlation between Thoracic and Lumbar Curves with Balance, Falling and Fear of Falling in Elderly - Zahra Mohammadi; Abdolkarim Karimi; Khorshid Parsapour; Hamzeh Baharlouei (Vesnu Publications, 2016)
Introduction: Falling is one of the major concerns among elderly population that has several consequences like hip fracture, head injury and even death. Changes in lumbar and thoracic curves are also common in elderly. There are limited number of studies investigating the association between lumbar curve and balance and fear of falling; additionally, some studies showed direct correlation between kyphosis and balance although some other studies did not confirm this correlation. The aim of the present study was investigating the correlation between lumbar and thoracic curves with balance, falling and fear of falling in elderly. Materials and Methods: The subjects were 47 aged male and female. A flexible ruler was used to measure spinal curves and Berg Balance Scale (BBS), Timed Up and Go (TUG) and Fall Efficacy Scale-International (FES-I) were used to measure balance and fear of falling, respectively. Results: The Pearson correlation coefficient showed significant correlation between spinal curves and BBS, TUG and FES-I. Conclusion: These findings showed that there was correlation between thoracic and lumbar curves with balance, and fear of falling.